(untitled) (Journal of the College of Basic Education, 2020)
In human societies all. We find the object of the reciprocal process among individuals in the area of satisfying living needs in different forms ، they differed that in their features but it is a function of consumption act satisfies the needs of the individual and meets his desires according to to socially acceptable behavior standards. We also find the contrast in the consumer process images it results from the severe needs of individuals from direction ، and the nature of the social environment place and time by which the mode of interaction in the sphere of consumption is determined from the direction. This method is scaled from barter to monetary operation which is the primary tool in the exchange process economic in modern society. Thus the monetary value expresses the value attributes of something. And with the pluralism of the names of the monetary process entirety, it feeds social life with special dynamics. The socio-economic process is essential for the joints of the social system . Phenotypic consumption plays an indicative role in the nature of economic activities in society commensurate with the need for profit. the form in which this type of consumption is an essential characteristic of the social behavior of the individual in modern society , in this context we find attention to and phenotypic things agreed it varies in size depending on different areas of life factors affecting it vary .